Perception and Practice Regarding Prevention of COVID-19 among Community People During and After Lockdown (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Due to erratic growth of COVID-19 infection across the globe, the mortality and morbidity due to COVID-19 is rapidly changing across the world. An assessment of the perception and practices of community members is important to reduce the risk for COVID-19 infection. Therefore, this study aims to assess the perception and practice regarding prevention of COVID-19 infection among community people before and after lockdown.MATERIALS AND METHODS: A cross-sectional study was conducted among community sample from November 2020 to January 2021 at Janakpur sub-metropolitan city of Dhanusha district, Province-2, Nepal. Two stage random sampling technique was used to select the study sample (n=422). A structured questionnaire was administered. McNemar Chi-square test was used to assess the association of perception and practice regarding prevention of COVID-19 infection during and after lockdown. P-values less than 0.05 were considered as significant.RESULTS: The perception among community people regarding prevention of COVID-19 infection during and after lockdown was insignificant for all the component (p>0.05) except perception regarding preventive measures against COVID-19; p=0.002 whereas the practices for prevention of COVID-19 infection among community people for all the components during and after lockdown was found to be significant (p